Port Logistics Integration: Challenges and ‎Approaches - Ali Alavi; Hong-Oanh Nguyen; Jiangang Fei; Jafar Sayareh (International Journal of Supply Chain Management, 2018)
The competitiveness of a seaport highly depends on its efficiency especially in terms of logistics practices, functions and activities and how all that is integrated with those of the other players in the supply chain.Despite the well-articulated importance of ports and terminals in integrated logistics, research on the success factors of port logistics integration remains scattered. The objective of this paper is to provide a review of the literature and based on this; provide an insight into how seaports and terminals may improve their logistics integration. A structured analysis of 78 papers published in Scopus indexed journals in logistics, supply chain and port management during the period 2000-2018 is conducted. A multidimensional conceptual framework for port logistics integration is proposed to incorporate the role of the three infrastructural variables emerging from the recent developments in the port logistics environment. The literature review has found the logistics process and operations, information integration, value-added services, and logistics practices being influential factors in logistics integration. Based on the research discussion and conclusion which is drawn from the literature review offer a basis for future research, both in respect of research approaches, concept definition and the select of theoretical foundation. The framework could be more detailed on each factor and consider actors perspective. Further testing and examination of the framework are needed for the validity of the results. This study questioned current literature in port logistics integration, highlight role infrastructural factors and the actor's role in the port logistics chain.